Penelitian Persepsi Dan Penerapan Kompetensi Alumni Pelatihan Pengelolaan Barang/Jasa Pemerintah (PBJP) Level-1 - Eddy Siswanto (Bajang Institute, 2026)
Level-1 Government Procurement of Goods/Services (PBJP) training is one of the strategies for developing the competencies of government personnel to support effective, efficient, transparent, and accountable procurement governance. This article presents a scientific study of alumni perceptions of the training and the implementation of the competencies acquired in the workplace. The study employed a descriptive approach with case study analysis, supported by a literature review. Data were collected through a questionnaire developed based on the constructs of the Health Belief Model (HBM), including perceived benefits, perceived barriers, self-efficacy, and cues to action. The results showed that most respondents had positive perceptions of the training and acknowledged its benefits in improving their basic understanding of government procurement. However, all respondents indicated that the training had not fully met the practical competency needs required in their work. The level of competency implementation varied across training topics, with basic materials being easier to apply than technical and strategic materials. The main factors influencing competency implementation included work experience, job relevance, opportunities for practice, and organizational support. These findings highlight the need to strengthen application-oriented materials, provide advanced training, and integrate training with work assignments to improve the transfer of competencies to the workplace